Silício e amônio na nutrição e no crescimento de brássicas - Barreto, Claudio Ferreira [UNESP] (2015)
The response of the brassica to ammonia nitrogen in the nutrient solution can be enhanced with the addition of silicon in the solution depending on the cultivated species. It aimed to evaluate the interaction of ammonium with silicon on nutrition, physiology and development of plants in two brassicas. A completely randomized design with four repetitions was used in a factorial 5 x 2, corresponding to five ammonium concentrations (1.3, 2.7, 5.5, 8.3 and 11.1mmol L-1) in absence and presence of silicon (1.0 mmol L-1). The following evaluations were performed: green index, accumulation of nitrogen, potassium, calcium, magnesium and silicon, in the root and shoot, photosynthesis, stomatal conductance, transpiration, stem diameter, height, leaf area, fresh and dry weight of shoot and root. Nutritive solution Si supply enhances broccoli plants growth response to ammonium, with no effect on cabbage. For broccoli and cabbage cultivation, ammonium concentrations of 8.6 and 7.3 mmol L-1 are indicated, respectively, with silicon association only for broccoli